Association Between Fertility Treatment and Cancer Risk in Children - Yuliana, Yuliana; Vera, Vera (The International Journal of Medical Science and Health Research, 2024)
Background: The association between fertility treatment and cancer risk in children has garnered increasing attention in recent years, as advancements in reproductive technologies have raised important questions regarding the long-term health outcomes of children conceived through these methods. Literature Review: The literature reveals a complex interplay of factors that contribute to understanding this relationship, as evidenced by the diverse studies reviewed. The foundational work by (Breit, 2014) emphasizes the critical role of fertility preservation in pediatric oncology and underscores the need for healthcare providers to be well-informed about the implications of fertility treatments. This is particularly relevant given the limited empirical evidence available regarding the direct correlation between fertility treatments and cancer risk in pediatric populations. Conclusion: In conclusion, the literature illustrates the complex and multifaceted nature of the association between fertility treatment and cancer risk in children. It highlights the need for ongoing research to clarify these relationships and underscores the importance of individualized care and equitable access to fertility preservation options. The findings collectively advocate for a more robust dialogue within the medical community to inform clinical practices and patient counseling regarding the potential risks and benefits associated with fertility treatments.